High‐Performance, Low‐Cost, and Dense‐Structure Electrodes with High Mass Loading for Lithium‐Ion Batteries. (11th July 2019) - Wu, Xinsheng; Xia, Shuixin; Huang, Yuanqi; Hu, Xiangchen; Yuan, Biao; Chen, Shaojie; Yu, Yi; Liu, Wei
Abstract: Lithium‐ion batteries have undergone a remarkable development in the past 30 years. However, conventional electrodes are insufficient for the ever‐increasing demand of high‐energy batteries. Here, reported is a thick electrode with a dense structure, as an alternative to the commonly recognized porous framework. A low‐temperature sintering technology with the aid of aqueous solvent, high pressure, and an ion‐conductive additive is originally developed for preparing the LiCoO2 (LCO)/Li4 Ti5 O12 (LTO) dense‐structure electrode as the representative cathode/anode material. The 400 µm thick cathode with 110 mg cm −2 mass loading achieves a high specific capacity of 131.2 mAh g −1 with a good capacity retention of 96% over 150 cycles, far exceeding the commercial counterpart (≈40 µm) of 54.1 mAh g −1 with 39%. The ultrathick electrode of 1300 µm thickness presents a remarkable area capacity of 28.6 mAh cm −2 that is 16 times that of the commercial electrode. The full cell based on the dense electrodes delivers an extremely high areal capacity of 14.4 mAh cm −2 . The ion‐diffusion coefficients of the densely sintered electrodes increase by nearly three orders of magnitude. This design opens up a new avenue for scalable and sustainable material manufacturing towards various practical applications. Abstract : Dense electrodes with high mass loading by a low‐temperature sintering technology with the aid of aqueous solvent and ion‐conductive nanoparticles are prepared. The dense electrode of 1300 µm in half cells delivers an extremely high areal capacity of 28.6 mAh cm –2 that is 16 times higher than that of its commercial counterparts. The capacity of full cells reaches 14.4 mAh cm –2 .